A Systematic Review : Well-being Therapy - Venty Ratnasari Telaumbanua; Ananta Yudiharso (Universitas Muhammadiyah Jember, 2020)
Well-being therapy is one of the relatively new interventions that used to achieve optimal and balanced functioning in certain dimensions of the individual. The aim of this study is to determine the effectiveness of well-being therapy applied in several contexts and in different age categories. Review was conducted in 14 studies based on inclusion and exclusion criterias. The results of the review indicate that well-being therapy can be carried out in the adult and student age categories, affective disorder and addiction cases, as well as preventive and curative treatments. Well-being therapy will also achieve maximum results if combined with with CBT treatment. However, there also need to consider about the number of sessions and the duration, and the severity of individual disorders so that the client can follow all the therapeutic process.